Beyond Numbers: An IPA Study of Accountability in Religious Tourism Governance at the Sunan Bonang Shrine - Farhani Kautsar Nugraha; Naghsa Arriva Puji Astuti; Ike Nur Syafitri; Rofino Baitul Akbar (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study explores the meaning of accountability in the management of religious tourism at the Sunan Bonang tomb complex in Tuban, East Java. Using a qualitative approach with an Interpretative Phenomenological Analysis (IPA) design, this research examines how site managers interpret and practice accountability within their religious and socio-cultural environment. Data were collected through semi-structured in-depth interviews with the Secretary of the Makbarot Sunan Bonang Foundation. Data credibility was enhanced through member checking and researcher reflexivity throughout the interpretative process. The findings show that accountability is deeply rooted in local spiritual and cultural values. Financial reporting is practiced as a form of social piety and dual responsibility: vertically to God and horizontally to the community. Four major themes emerged from the study: (1) spirituality as the foundation of management, (2) financial reporting as moral trust, (3) tensions between tradition and digitalization, and (4) community autonomy in relation to the state. The study concludes that accountability in religious tourism spaces manifests in distinctive ways that transcend formal institutional frameworks while still emphasizing transparency, trust, and social responsibility. The findings contribute to the accountability literature by demonstrating how local spiritual values shape accountability practices beyond formal and technocratic frameworks. Practically, the study highlights the importance of accommodating community-based and culturally embedded forms of accountability in the governance of religious tourism destinations.